Cricket Data Visualisation App - Jose, Kevin (Wellington Faculty of Engineering Symposium, 2023)
Cricket is a complex sport that provides a great wealth of online data for potential analysis and discoveries. The problem is that this data is not very accessible or digestible because it is presented in a tabular format and in large amounts. The purpose of this project was to investigate and implement a web application that enables users to visualise batting data in men’s ODI cricket. The impacts of this data visualisation app are that users can easily learn more about cricket and its rich history by discovering patterns and trends in the data. This will give fans a greater appreciation for the sport, in addition to educating those who are new to cricket and wish to learn more.